The Relationship between Patient Satisfaction and Family Support with Patient Blood Pressure Control Compliance at Long Mesangat Public Health Center Year 2023 - Supatmi; Lukman Nulhakim; Tini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Hypertension is a health problem that requires good management, because of its high morbidity and mortality. Hypertension needs continuous treatment. Patient compliance with blood pressure control is needed as an effort to prevent hypertension. Patient control compliance will be influenced by satisfaction with the services provided. The aim of this study was to determine the relationship between patient satisfaction and family support with patient blood pressure control compliance at the Long Mesang Health Center in 2023. This study uses a correlation research design with a cross-sectional research design. The sample size in this study is 108 respondents. The results of the statistical test using the chi-square test obtained a p-value (0.000) < α value (0.05) between patient satisfaction and family support. So that Ha is accepted, which means there is a relationship between patient satisfaction and compliance with blood pressure control and there is a relationship between family support and compliance with blood pressure control.